Japan before 1800 - Kleine, Christoph (Companion to the Study of Secularity, 2018)
As in most premodern societies, prior to the accelerated modernisation of Japan under Western influence in the 19th century, concepts of societal differentiation were primarily focused on the relationship between religious and political institutions. It is important to note, however, that the conceptual distinctions found in discursive statements do not necessarily reflect or represent the actual state of societal differentiation. In many cases, these concepts were, in all likelihood, normative ideals that were only partly realised. Having said this, a very brief and generalising narrative of the relationship between ‘religion’ and ‘the secular’ would run as follows.